John Duns Scotus on Grace and the Trinitarian Missions - Kennard, Mitchell J., author.
1 online resource.
Keywords: In John Duns Scotus on Grace and the Trinitarian Missions, Mitchell J. Kennard argues that Franciscan theologian John Duns Scotus (d. 1308) has been wrongly inscribed in the narrative of the late medieval theology of grace. Scotus is presented here not as the initiation or cause of the low fourteenth-century theology of grace but as the last great contributor to the high thirteenth-century theology of grace as deifying participation in the divine nature. This book argues that Scotus’s signature reflections on the relationship between grace and the Trinitarian missions—the Incarnation of the Son and the indwelling of the Holy Spirit—warrant closer attention by both historical and systematic theologians alike.